Technique and protocols for cardiothoracic time-resolved contrast-enhanced magnetic resonance angiography sequences: a systematic review. Issue 2 (February 2021) - Zanardo, M.; Sardanelli, F.; Rainford, L.; Monti, C.B.; Murray, J.G.; Secchi, F.; Cradock, A.
Abstract : AIM: To review contrast medium administration protocols used for cardiothoracic applications of time-resolved, contrast-enhanced magnetic resonance angiography (MRA) sequences. MATERIALS AND METHODS: A systematic search of the literature (Medline/EMBASE) was performed to identify articles utilising time-resolved MRA sequences, focusing on type of sequence, adopted technical parameters, contrast agent (CA) issues, and acquisition workflow. Study design, year of publication, population, magnetic field strength, type, dose, and injection parameters of CA, as well as technical parameters of time-resolved MRA sequences were extracted. RESULTS: Of 117 retrieved articles, 16 matched the inclusion criteria. The study design was prospective in 9/16 (56%) articles, and study population ranged from 5 to 185 patients, for a total of 506 patients who underwent cardiothoracic time-resolved MRA. Magnetic field strength was 1.5 T in 13/16 (81%), and 3 T in 3/16 (19%) articles. The administered CA was gadobutrol (Gadovist) in 6/16 (37%) articles, gadopentetate dimeglumine (Magnevist) in 5/16 (31%), gadobenate dimeglumine (MultiHance) in 2/16 (13%), gadodiamide (Omniscan) in 2/16 (13%), gadofosveset trisodium (Ablavar, previously Vasovist) in 1/16 (6%). CA showed highly variable doses among studies: fixed amount or based on patient body weight (0.02–0.2 mmol/kg) and was injected with a flow rate ranging 1–5 ml/s. Sequences were TWIST in 13/16 (81%), TRICKS in 2/16 (13%), and CENTRA 1/16 articles (6%). CONCLUSION: Time-resolved MRA sequences were adopted in different clinical settings with a large spectrum of technical approaches, mostly in association with different CA dose, type, and injection method. Further studies in relation to specific clinical indications are warranted to provide a common standardised acquisition protocol. Highlights: A consensus on TR-MRA technique for cardiothoracic applications is not available. Factors affecting differences are mainly contrast agent dose and injection modality. Further studies are warranted to provide a common standardised acquisition protocol.